Controversial grammatical Issue related to Arabic particles with multiple meanings: Al-Sa’adi's viewpoints - Abdul Rahman, Mohammed Mouaz (Journal of Arabic Language Sciences and Literature, 2022)
The Position of Sheikh Al-Sa’adi from Argumentative Subjects in the Semantic Prepositions. The research explored the contentious grammatical issues in Al-Sa’adi’s book entitled: “التعليق وكشف النقاب على نظم قواعد الإعراب". It sought to shed some light on the author’s point of view on pertinent grammatical matters. It equally dealt with the most outstanding syntax related contentions between the Basran and Kufi grammarians, including later generation scholars such as Ibn Malik, Abu Hayyan, and Ibn Usfur. The study adopted a descriptive analytical approach whereby Al-Sa’adi’s viewpoints on crucial grammatical matters were sampled and critically analyzed. The study revealed that Al-Sa’adi had a firm grasp of the key controvertible grammatical issues and that he provided independent scholarly views and suggestions in some instances. On several occasions he agreed with both the classical and contemporary grammarians. Sometimes he would prefer the viewpoints of the Basran grammarians such as the use of (بلى) to affirm a negated utterance and sometimes he would opt for Kufi school such as the view that the nouns succeeding prepositions or adverbial places in grammatical structures are nominatives either as the agents of verbs or subject of a nominal sentence among other others. Sometimes, he opts for the view of a specific grammarian such as his agreement with Akhfash that word (إذ)-which signals suddenness- is a particle. Another example of the latter is his choice of Sibawaihi’s view that bounded pronouns that come after (لولا) are rendered genitive by the particle including Ibn Kisan’s view that the letters (أ) and (ل) both constitute definite article. Sometimes, he gives a general discussion of the key grammar issues, without taking a stance, for examples the rules pertaining to the use of (إنَّ) (ليس) and (ما) between Hijazis and the Tamimis. In general, Al-Saadi writings require further comprehensive linguistic explorations particularly in the areas of syntax and semantics.
Keywords: Al- Sa’adi, viewpoint; Huruful Ma’aani; Arabic particles; Controversial grammatical Issues